2021
DOI: 10.1158/1078-0432.ccr-21-2394
|View full text |Cite
|
Sign up to set email alerts
|

18F-FMISO PET Imaging Identifies Hypoxia and Immunosuppressive Tumor Microenvironments and Guides Targeted Evofosfamide Therapy in Tumors Refractory to PD-1 and CTLA-4 Inhibition

Abstract: Hypoxia is a well-known component of many tumors and acts in an immunosuppressive manner through multiple distinct pathways. 18 F-FMISO PET imaging has been demonstrated to accurately quantify hypoxia in a clinical setting, although it has not been investigated for immunotherapy. Our work demonstrates that effective immunotherapy prevents tumor hypoxia and that uptake of 18 F-FMISO was predictive of subsequent changes in anatomical tumor size. We further demonstrate that PET imaging of hypoxia is correlated wi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 37 publications
0
16
0
Order By: Relevance
“…In addition, 18F-FMISO PET imaging was also applied in preclinical models of breast and colon cancer to probe the tumor and its surrounding microenvironment before and during PD-1 and CTLA-4 checkpoint blockade to quantify tumor hypoxia. Hypoxic signals from PET imaging are used to add hypoxia-targeted therapy to unresponsive tumor, which ultimately provides therapeutic synergy [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, 18F-FMISO PET imaging was also applied in preclinical models of breast and colon cancer to probe the tumor and its surrounding microenvironment before and during PD-1 and CTLA-4 checkpoint blockade to quantify tumor hypoxia. Hypoxic signals from PET imaging are used to add hypoxia-targeted therapy to unresponsive tumor, which ultimately provides therapeutic synergy [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…PET agents are radioactive compounds quantitatively measurable through their beta-decay, which is converted into a 3D image. Intratumoral hypoxia has been detected via PET by utilizing nitroimidazole isotopes, such as 18 F-fluoromisonidazole 18 F-FMISO and 18 F-EF5, which irreversibly bind to thiol groups on metabolic proteins at rates inversely proportional to O 2 concentrations [ 107 ]. Hirata et al recently reported that 18 F-FMISO provides valuable prognostic data on survival and treatment response for patients with glioma and information on necrosis, vascularization, and permeability of the tumor [ 108 ].…”
Section: Detection Of Hypoxia In Vivomentioning
confidence: 99%
“…18 F-fluoromisonidazole ( 18 F-FMISO) is a PET tracer that selectively binds to hypoxic tissues and can be used to measure the hypoxia in glioma and provide information for prognosis [ 90 ] . As it is retained by irreversible binding to the thiol-rich metabolic proteins at rates that are inversely proportional to oxygen concentration, 18 F-FMISO provides quantitative measurements of hypoxia level [ 91 ] .…”
Section: Positron Emission Tomography Tracers For Gliomamentioning
confidence: 99%